CPC-079 Management of Myelodisplastic Syndromes and Lymphomas: The Example of Lenalidomide. (12th March 2013) - Scaldaferri, M; Sciorsci, E; Re, F; Calvo, C; Chiumente, M; Barilà, D; Chiesa, A; Ferroni, M; Stecca, S; Cattel, F
Abstract : Background: At our centre, haematologists and department pharmacists constantly monitor outcomes and safety of treatment with lenalidomide. Purpose: To describe clinical outcomes and safety of lenalidomide in our lymphoma and myelodysplastic syndrome patients. Materials and Methods: Onco-AIFA Registry and medical records were checked as of 30/06/2012 for diagnosis, duration of treatment, incidence of adverse drug events (ADRs). Results: Data of 34 patients were reviewed, with the following diagnoses: Diffuse large B-cell lymphoma (DLBCL), 24 patients; 5q-myelodysplastic syndrome (MDS5q-), 11 patients and mantle cell lymphoma (MCL), one patient. Of patients with DLBCL, one discontinued treatment because of serious ADRs, two because of death and 4 for disease progression after an average of 4.4 treatment cycles, corresponding to 7 months (range: 2–18). Of patients with MDS5q-, 8 stopped treatment, two of whom because of disease progression or death and two for toxicity. The median duration of treatment was 11.8 cycles (range 1–29). Seventeen DLBCL patients and 3 MDS5q- patients are still on therapy. 34 non-serious ADRs relating to 14 patients and 5 serious ADRs relating to 4 patients were reported, two of which were cases of development of solid neoplasia. Non-serious ADRs were mostly cases of haematological toxicity, alterations of the skin and of nervous system and infections. Conclusions: Lenalidomide seems to control the disease in patients with MDS5q- for long periods, while the Time to Progression in patients with DLBCL appears shorter. The treatment-related toxicity appears in most cases acceptable. Despite the limited number of data, our analysis highlights the need for close monitoring of the patients both during treatment and on follow-up, as evidenced by the two cases of onset of neoplasia. The progressive collection of data is providing the haematologists and pharmacists the information to design a model for optimised appropriate treatment with lenalidomide. No conflict of interest.